BOOK REVIEW: THE CAMBRIDGE HANDBOOK OF BIOLINGUISTICS - Himawan, Riswanda; Santosa, Anang; Rahayu, Triwati; Shodiq, Ja’far (LLT Journal: A Journal on Language and Language Teaching, 2025)
This review discusses the implementation of biolinguistics in children’s language acquisition. The focus lies on the importance of biolinguistics in studying children’s language acquisition. Children’s language is considered important because, within the scientific concept of biolinguistics, will have an influence on the development of children’s language until the child is an adult. This review is based on The Cambridge Handbook of Biolinguistics, which consists of three parts. The first section discusses the history of biolinguistics; the second chapter discusses the mind, brain and behavior in relation to language; and the third section discusses the evolution of language.  This book aims to open our horizons about biolinguistics as a science that harmonizes language and knowledge, language development in children and the evolution of language in various species. In addition, the most profound meaning of this book lies in its emphasis on the function the human brain,  where each part has its own specific role. Through this book we are asked to be grateful for God's gift to humans for giving the brain with a very extraordinary function. In line with its purpose, this book not only examines the integration between language and the human brain, but also inspires readers to appreciate the complexity of human cognition.